2016
DOI: 10.1371/journal.pone.0156465
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Predictors of Refractory Mycoplasma pneumoniae Pneumonia in Children

Abstract: ObjectiveTo analyze the clinical characteristics of refracory Mycoplasma pneumoniae pneumonia (RMPP), and explore the related factors predicting RMPP.MethodsRetrospective analysis was performed on 634 children with Mycoplasma pneumoniae pneumonia (MPP) hospitalized in our hospital between January 1, 2011 and December 31, 2014. The clinical features, laboratory data, radiological findings between the RMPP group and the general Mycoplasma pneumoniae pneumonia (GMPP) group were compared and the predictive values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
148
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 32 publications
(35 reference statements)
22
148
2
1
Order By: Relevance
“…What is more, our study mainly focused on the clinical, laboratory, and radiological features of children while the baseline information was not significantly different in this study. One previous study showed that the median age was significantly different between the GMPP and RMPP groups, although it was not found to be an independent risk factor 8 . We still need to pay attention to the relevant baseline information and update our model in the future.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…What is more, our study mainly focused on the clinical, laboratory, and radiological features of children while the baseline information was not significantly different in this study. One previous study showed that the median age was significantly different between the GMPP and RMPP groups, although it was not found to be an independent risk factor 8 . We still need to pay attention to the relevant baseline information and update our model in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Although the mechanism of RMPP is not clear, it is widely accepted that inflammatory reactions and immune responses may play an important role in the progress of RMPP. Biomarkers related to inflammatory reactions were evaluated by previous studies 8–12 . CRP, LDH, and IL‐6 were found to be associated with high risk of RMPP in children through an ordinal logistic regression procedure 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH was a variable that is universally elevated in many pulmonary diseases and was reported to be associated with disease severity in several studies1415. Previous studies had identified higher levels of LDH as a risk factor for RMPP161718. CRP is a gross biochemical index of inflammation and is used commonly in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiography was performed before admission or during hospitalization using standard equipment and radiographic techniques. Large lesion was defined when the extent of infiltration on chest radiography was more than 1/3 of the lung21. All patients were treated initially with macrolides (azithromycin or erythromycin) for 5–7 consecutive days or partly with beta-lactam antibiotics (ampicillin with sulbactam or ceftriaxone) simultaneously.…”
Section: Methodsmentioning
confidence: 99%